The gains from economic integration. (25th May 2019) - Comerford, David; Rodríguez Mora, José V
Summary: This paper measures the effect of political integration, such as sharing a national state or economic union, on the degree of trade integration. Consistently with previous work, we find large border effects. However, such estimates may be biased and overestimate the effects of borders because of endogeneity: selection into sharing a political space is correlated with affinities for trade. We propose a method to address this and we produce estimates which are closer to the causal effect. We then conduct speculative exercises showing the costs and benefits of the changing levels of integration associated with: the independence of Scotland, Catalonia and the Basque Country from the United Kingdom and Spain [but remaining within the European Union (EU)]; the United Kingdom's exit from the EU; the break-up of the EU itself and closer integration within the EU so that its internal borders appear similar to the internal borders of individual countries (as opposed to its current state of being simply a closely integrated group of countries). We find that the border effect between countries is an order of magnitude larger than the border effect associated with the EU.